Decreased Fibrinolysis in Reperfused Ischaemic Tissue - Cherry, G. W; Ryan, T. J; Ellis, J. E (Thrombosis and Haemostasis, 1974)
The fibrinolytic activity of skin flaps subjected to ischaemia and reperfusion was studied in five pigs. Total interference with the blood supply up to 24 hours did not in itself lead to changes in fibrinolytic activity. However, reperfusion of the skin after six hours of ischaemia caused a dramatic reduction in fibrinolytic activity measured 18 hours later.Similar studies on reperfused femoral artery and vein after six hours of ischaemia showed marked reduction in fibrinolytic activity of the vessels.It is suggested that reperfusion of tissue made ischaemic for six hours is damaging and might be a contributory factor to vascular pathology.